A realidade da ficção: ambiguidades literárias e sociais em O Mulato de Aluísio Azevedo - Almeida, Rodrigo Estramanho de (2010)
This thesis is an analysis of the novel O Mulato (1881) of Aluísio Azevedo (1857-1913) which seeks to study the points of contact work and the author with the Brazilian reality of the nineteenth century. In the proposed study, the central idea is, by analyzing the plot of the novel, defining the scope of the similarities between art, politics and society. With this objective will analyze the approach the author with the isms of his time, such as naturalism, positivism, anticlericalism and republicanism. Still, through internal analysis of O Mulato, networks will be analyzed to formulate that sense sociopolitical typologies for understanding and knowledge of the ambiguities of the narrative, therefore trying to uncover the networks of meaning and strategies of language to the configuration of reality own text. This will provide detailed notions of reality from the fiction of O Mulato in relation to the Brazilian's second reign ends and demonstrate that it is possible to achieve a more general interpretation of the novel in relation to the social structure of the period